No association between vitamin D deficiency and markers of mone health in athletes - Allison, R. J.; Farooq, A.; Hamilton, B.; Close, G. L.; Wilson, M. G. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Adequate vitamin D (25(OH)D) is required to maintain good bone health, yet many athletes are 25(OH)D deficient. This study sought to examine the relation between serum 25(OH)D and measures of bone health (bone mineral density (BMD) and T-score) in an ethnically diverse athletic population.